From Ritual Space to Digital Presence: Community-Driven Preservation of Luoyang's Ancient Architecture through Immersive Technologies - Li , Bo; Laoakka, Sastra; Champadaeng, Sitthisak (Journal of Dhamma for Life, 2025)
This study investigates the historical and cultural significance of ancient architecture in Luoyang, a city renowned for its rich heritage and dynastic legacies. It critically examines current conservation efforts, highlighting their emphasis on material preservation through expert-led interventions. While effective in mitigating physical decay, these conventional strategies often marginalize the intangible cultural elements—such as spatial rituals, collective memory, and local narratives—that give these structures enduring meaning. Furthermore, limited public participation, especially among younger generations, has led to a growing disconnect between heritage sites and contemporary society. To address these challenges, the research adopts a mixed-methods approach, combining historical analysis, stakeholder interviews, and case studies of digitally supported heritage projects. The study population includes conservation experts, local residents, educators, and tourists, with selected sample groups engaged through participatory workshops and surveys. Research tools include digital ethnography, 3D scanning, and immersive media (VR/AR) prototyping, enabling both qualitative and experiential data collection. Findings reveal that digital technologies hold transformative potential when used not merely for visualization but as platforms for cultural activation and emotional storytelling. By recontextualizing ancient architecture as dynamic cultural interfaces, the study proposes innovative models that integrate digital heritage with creative education and participatory tourism. These strategies aim to foster sustainable preservation while deepening public engagement and intergenerational transmission of cultural values. Ultimately, the research advocates for a shift from form-focused conservation to a more holistic, community-centered preservation paradigm.